2002
DOI: 10.1177/088307380201700211
|View full text |Cite
|
Sign up to set email alerts
|

Asperger's Syndrome and Cortical Neuropathology

Abstract: Asperger's disorder or syndrome is characterized by impaired social interaction, normal intelligence, and adequate language skills in the areas of grammar and vocabulary. The symptoms are pervasive in nature and usually manifested in childhood. Despite the gravity and chronicity of the condition, the medical literature remains sparse and offers no information about possible neuropathologic underpinnings. The present study is a case report on two patients with Asperger's syndrome. Neuropathologic examination re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 21 publications
5
41
0
2
Order By: Relevance
“…Recent arguments for the latter proposition arose from the discovery of abnormal spatial organization and density of cortical cells both in the frontal cortex (area 9) and in the temporal cortex (areas 21 and 22) in autism and Asperger syndrome (Casanova, Buxoeveden, Switala, & Roy, 2002a, 2002b.…”
Section: Discussionmentioning
confidence: 99%
“…Recent arguments for the latter proposition arose from the discovery of abnormal spatial organization and density of cortical cells both in the frontal cortex (area 9) and in the temporal cortex (areas 21 and 22) in autism and Asperger syndrome (Casanova, Buxoeveden, Switala, & Roy, 2002a, 2002b.…”
Section: Discussionmentioning
confidence: 99%
“…See table 2 for a summary of these data. For example, some studies have found reduced neuropil space and narrower minicolumn width in frontal and temporal brain regions in ASD (Buxhoeveden et al, 2007;Casanova, Buxhoeveden, Switala, & Roy, 2002a;Casanova, Buxhoeveden, Switala, & Roy, 2002b;Casanova et al, 2006), whereas a recent study has reported wider minicolumns in sensory, frontal and parietal cortical areas in ASD (McKavanagh, Buckley, & Chance, 2015).…”
Section: Cortical Minicolumnsmentioning
confidence: 99%
“…Another neuropathologic study had indicated abnor- malities in the mini columnar organization of neurons in patients with AS and autism subjects, which could possibly lead to overconnected and insufficiently inhibited neural networks. 22 Areas of aberrant white matter, evaluated by diffusion tensor imaging, were reported between regions activated in the theory of mind tests, including the anterior cingulate and amygdala. 23 On the other hand, another study reported smaller anterior cingulate volumes related to lower metabolic activity.…”
Section: Discussionmentioning
confidence: 99%